Intussusception secondary to Peutz-Jeghers syndrome: a case report and literature review of diagnostic and therapeutic advances - Zhang, Jing; Xie, Tian-Hao; Fu, Yan; Jin, Xiao-Shi; Wang, Qiang; Niu, Zheng (Frontiers in Medicine, 2025)
Peutz-Jeghers syndrome (PJS) is a rare autosomal dominant genetic disorder characterized by gastrointestinal hamartomatous polyposis and mucocutaneous pigmentation, predisposing patients to malignancies. This article reports a case of a 19-year-old male presenting with recurrent abdominal pain, diagnosed with small intestinal intussusception secondary to PJS polyps. Computed tomography revealed the “double-ring sign,” indicative of intussusception, and laparoscopic exploration confirmed multiple small intestinal polyps, which were subsequently resected. Postoperative pathology confirmed the diagnosis of PJS. The article reviews the diagnostic criteria, genetic basis, clinical manifestations, and recent advances in the management of PJS. It highlights the transformation in management strategies, driven by advancements in genetic testing, endoscopic interventions, and multidisciplinary collaboration. Early diagnosis, genetic screening for first-degree relatives, and lifelong surveillance are emphasized to mitigate the risk of malignancies and improve patient outcomes. The refinement of diagnostic criteria, genotype–phenotype correlations, and innovations in endoscopic techniques are discussed, underscoring their role in optimizing therapeutic approaches.